2013
DOI: 10.1161/strokeaha.113.000780
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Minocycline in Acute Stroke

Abstract: Background and Purpose-Minocycline, in animal models and 2 small randomized controlled human trials, is a promising neuroprotective agent in acute stroke. We analyzed the efficacy and safety of intravenous minocycline in acute ischemic and hemorrhagic stroke. Methods-A multicenter prospective randomized open-label blinded end point evaluation pilot study of minocycline 100 mg administered intravenously, commenced within 24 hours of onset of stroke, and continued 12 hourly for a total of 5 doses, versus no mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 24 publications
0
76
0
Order By: Relevance
“…In a recent pilot study the use of intravenous-administered minocycline in a small sample of acute ischemic and hemorrhagic stroke patients has proven to be safe but not efficacious [85], although scalability and a relative delay in administration (within 24 h after onset) could account for this.…”
Section: New Developments and Future Conceptsmentioning
confidence: 99%
“…In a recent pilot study the use of intravenous-administered minocycline in a small sample of acute ischemic and hemorrhagic stroke patients has proven to be safe but not efficacious [85], although scalability and a relative delay in administration (within 24 h after onset) could account for this.…”
Section: New Developments and Future Conceptsmentioning
confidence: 99%
“…They showed that patients taking minocycline showed a significant decrease in NIHSS (10). This is despite the fact that in a pilot study, Kohler et al studied the effect of an intravenous dose of minocycline 100 mg over 24 hours after stroke and every 12 hours, consecutively in the stroke patients, and showed that minocycline was a safe drug but not effective (11). It seems that because the dose used and route of administration in this study was different with the current study, this difference is justified.…”
Section: Discussionmentioning
confidence: 99%
“…Lamp et al showed that minocycline caused a significant de-crease in NIHSS (10). Kohler et al showed that minocycline in stroke is a drug safe but not effective treatment option (11). Therefore, the purpose of this clinical trial was to evaluate the efficacy of minocycline in the recovery of patients with acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The same treatment paradigm was also utilized by Amiri-Nikpour et al who reported improved NIHSS scores at 30, 60 and 90 days post-AIS in male patients receiving minocycline [233]. Kohler et al utilized lower doses of minocycline (ive 100 mg doses) and saw no improvement in NIHSS at 7 days nor in the mRS or BI at 90 days post-AIS [234].…”
Section: The Antibiotic Minocycline In Ais and Tbimentioning
confidence: 91%